Karl Marx: a determinação ontonegativa originária do valor - Cotrim, Ivan (2008)
Our purpose with this work is to demonstrate that Marx s discovery of the ontologically negative determination of value takes place back in his earliest critique on political economy. Marx s critical analysis aims directly at private property, labor division, and wage labor: all forms that express themselves in value. The reproduction of these conditions leads necessarily to preservation of class opposition, as well as estrangement and alienation. We showed that political economy, whose position is radically opposed to Marx s, assumes value as a positive determination along its one hundred and fifty years trajectory culminating in Smith and Ricardo. While the ontologically negative determination of value, set by Marx, takes value as alien to human essentiality, political economy, by advocating the positive character of value, assumes it as a form of being inherent to individuals, though paying the price of not recognizing alienation and estrangement which correspond to it. The foundations of political economy traces back to conceptions that assign innate features to human being: either state of nature or moral sentiments and economical acting. On the contrary, in Marx s view men are selfconstructed through their practical activity, producing both their objective world and subjectivity